Preparation of BSA-coated Au Nanoparticles Contrast Agent and Its Application in PETCT Imaging: BSA-coated Au Nanoparticles Contrast and PETCT Imaging - Wei, Jing; Li, Pingwei; Zhang, Huai; Zhu, Ronghua (Cellular and Molecular Biology, 2022)
Tumors are the biggest opponents in the history of human diseases, and they cannot be eliminated so far. The only way to treat tumors is to detect them early so that the survival rate can be improved by early treatment. For tumor detection, CT scan is the most commonly used, and PET/CT is an enhanced version of CT technology. Although PET/CT can produce relatively clear images of the human body, due to the complex structure of the human body, there are many ghosts and shadows, and the images cannot be accurately judged. Therefore, this paper aims to prepare high-definition nanoparticle contrast agents, hoping to make PET/CT images clearer and easier to distinguish. In this paper, the advantages of gold nanoparticles are fully analyzed for the preparation of contrast agents, and a gold nano-contrast agent coated with bovine serum albumin (BSA) is proposed. Gold nanoparticles (GNRs) were prepared by the traditional induction method and their properties were analyzed. Finally, taking mice as the experimental object, a comparative experiment was carried out, and the toxicological and optical properties were analyzed. The experimental results show that the adsorption performance of the BSA-coated gold nanoparticles prepared in this paper is more than 90% at different temperatures. And through the comparison experiment, the contrast agent prepared in this paper has an increased signal-to-noise(StN) ratio change rate of more than 50%, which can be well applied to PET/CT imaging.